Uji Kadar Protein Dan Organoleptik Yoghurt Tempe DenganPenambahan Ekstrak Buah Nangka (Artocarpus heterophyllus) DanKonsentrasi Starter Yang Berbeda - Nisa, Shaldan Khoirun; , Dra. Hj. Suparti, M.Si (2015)
Tempe yoghurt (soybean cake yoghurt) is symbiotik drink that rich of protein made by adding lactic acid bacteria to the tempe (soybean cake) extract that has been added source of sugar. Starter bacteria activity can affect yoghurt protein content because it can produce protease enzymes that can break down proteins and additionally its beany flavor is not flavored by consumer. So it is needed the addition of fruit extracts to enhance the flavor, reduce beany flavor, and improve the nutritional value of tempe yoghurt (soybean cake yoghurt). This research aimed to determine the effect of jackfruit extracts and starter concentration toward protein level and tempe (soybean cake) yoghurt sense. The research is conducted in biology laboratory of Muhammadiyah University of Surakarta and Nutrition Food Laboratory of Agriculture Faculty of Sebelas Maret University of Surakarta. Research design uses Complete Random Design (RAL) consist of two factor. The first factor of jackfruit extract (N) three levels of treatment are 0%, 15%, 30%. The second factor of starter concentration consist of three level treatment are 3%, 5%, 7%. Data analysis is done by kruskal-wallis to protein content and organoleptic descriptively and receptivity. The result of research shows the higest protein level contained in N1K1 treatment (jackfruit extract of 15% and starter concentration do not affect toward protein contain, but it happened the best interaction are N2K2 (jackfruit extract of 30% and starterconcentration 5%) get pleasure level of panelist toward texture 4,00 (thick), color 4,30 (yellow), aroma 4,45 (specific yoghurt), flavor 4,70 (sweet acidic) and receptivity.